Electromagnetic probes of fundamental physics : (World Scientific, 2003)
This book constitutes the proceedings of a workshop which originated from a discussion with Professor A Zichichi in March 2001. The purpose of the meeting was to celebrate two developments at Brookhaven that, in both cases, are the outcome of more than a decade of preparation: the new muon g-2 measurement and the flood of data that started pouring out of RHIC. Bringing together people from these very different fields was an interesting challenge. But, at the time, when a small community of heavy ion physicists was beginning to define a program of electromagnetic interactions at RHIC and LHC, it seemed logical.